Analysis of the Effect of Magnetic Thickness and Rotating Speed on PMSG 24 Slot 16 Pole Characteristics - Achiruddin Lubis; Zulfatri Aini (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
Wind energy is one of the alternative energies that can overcome global warming caused by fossil energy. Permanent Magnet Synchronous Generator (PMSG) has a higher efficiency compared to other types of generators. The previous permanent magnet synchronous generator model was only able to produce efficiency at a rotational speed of 500 rpm of 67.30% and at a rotational speed of 1500 rpm of 80.9%, so further research is needed to get a higher efficiency value. This study aims to analyze the effect of magnetic thickness and rotational speed on PMSG characteristics and obtain a higher efficiency value. Using variations in magnetic thickness of 7.5mm, 9 mm, and 10 mm and variations in rotational speed of 500 rpm, 1000 rpm,  and 1500 rpm using software based on Finite Element Methode, this study obtained the results of the largest current, voltage, input power, and output power at a magnetic thickness of 10mm with a rotational speed of 1500 rpm of 20.40 A, 204.06 V, 4979.60 W, and 4266.21 W, with the greatest efficiency being in the magnetic thickness of 9mm and 10 rpm of 89.20%